Historical Perspective on Spiritual Education in Australian Schools Part I: The Contribution of Religious Education - Rossiter, Graham (Journal of Christian education, 2011)
This is the first of two articles devoted to an historical perspective on spiritual education in Australian schools. It begins with an understanding of what is meant by spiritual education and a brief outline of its historical context. It then proceeds to develop the proposition that religious education has been the main area of the school curriculum in which a spiritual and moral dimension has been addressed. This is achieved by a ‘big picture’ historical perspective on religious education in Government schools and the interrelation between religion studies and denominational religious education. Attention is drawn to an emerging initiative which is the subject of the subsequent article.